The Effect of Packaging Materials on Postharvest Quality of Salak Fruit Cultivar Pondoh (Salacca edulis Reinw.) - Desi Sekar Utami; Iffah Muflihati; Enny Purwati Nurlaili; Arief Rakhman Affandi (Universitas PGRI Semarang, 2020)
Salak fruit is generally considered to have a short storage life, because it is perishable fruit. The objective of this study was to investigate the effect of packaging material on the quality of salak fruit cultivar pondoh. In this research salak fruits were packaged in the three types of packaging materials: polyethylene plastic bags (PE), cardboard (CB), and bamboo baskets (BB), and it were stored at 26oC. Parameters of the research were considered in mass loss, water content, total soluble solid, and titratable acidity. The result of the research showed that packaging salak pondoh with polyethylene plastic bag has better quality than other packaging materials and can prolong its shelf life.